2004
DOI: 10.1086/421944
|View full text |Cite
|
Sign up to set email alerts
|

 -D-Glucan as a Diagnostic Adjunct for Invasive Fungal Infections: Validation, Cutoff Development, and Performance in Patients with Acute Myelogenous Leukemia and Myelodysplastic Syndrome

Abstract: The Glucatell (1r3)-b-D-glucan (BG) detection assay (Associates of Cape Cod) was studied as a diagnostic adjunct for invasive fungal infections (IFIs). On the basis of findings from a preliminary study of 30 candidemic subjects and 30 healthy adults, a serum BG level of у60 pg/mL was chosen as the cutoff. Testing was performed with serial serum samples obtained from 283 subjects with acute myeloid leukemia or myelodysplastic syndrome who were receiving antifungal prophylaxis. At least 1 serum sample was positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
410
5
19

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(451 citation statements)
references
References 27 publications
13
410
5
19
Order By: Relevance
“…As the design of these studies was very variable, only 10 (4 case-control and 6 cohort studies) [17][18][19][20][21][22][23][24][25][26] were considered appropriate for analysis on the basis of the following parameters: type of population (hematological patients), sample size (X20 IFD cases and X50 non-IFD controls) and reference standard of IFD (definition according to the EORTC/MSG criteria). 10 Whereas sensitivity, specificity, positive and negative predictive values derived from these analyses in hematological patients were variable (Table 3), no major differences were observed among the different assays.…”
Section: B-glucan (Bg)mentioning
confidence: 99%
See 1 more Smart Citation
“…As the design of these studies was very variable, only 10 (4 case-control and 6 cohort studies) [17][18][19][20][21][22][23][24][25][26] were considered appropriate for analysis on the basis of the following parameters: type of population (hematological patients), sample size (X20 IFD cases and X50 non-IFD controls) and reference standard of IFD (definition according to the EORTC/MSG criteria). 10 Whereas sensitivity, specificity, positive and negative predictive values derived from these analyses in hematological patients were variable (Table 3), no major differences were observed among the different assays.…”
Section: B-glucan (Bg)mentioning
confidence: 99%
“…21 The prerequisite of two consecutive positive tests for IFD diagnosis was investigated in four studies and resulted in a specificity approaching 100% and a lower sensitivity ranging between 45 and 65%. 17,19,23,26 The diagnostic performance of BG was similar in IC and IA, while utility in other less common IFD could not be assessed because of lacking data. Few data on the timing of BG positivity compared with conventional diagnostic tools are available: one study suggested that BG detection might precede IFD diagnosis according to the EORTC/MSG criteria.…”
Section: B-glucan (Bg)mentioning
confidence: 99%
“…5 With the exception of the Aspergillus-directed galactomannan enzyme immunoassay and 1,3-b-glucan detection assays, the serological kits available for the detection of fungal antigens have inconsistent sensitivity, specificity or both. [6][7][8][9][10][11] Thus, techniques with higher sensitivity and specificity for detection of fungal pathogens, such as fungus-specific DNA probes and the PCR assays, are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have established its diagnostic value in invasive candidiasis and invasive aspergillosis (9,10). However, currently numerous non-Candida and non-Aspergillus fungi are important causes of IFD in the immunocompromised host, and in this setting, clinical and mycological experience with the use of BG as a tool for diagnosis is scarce (7)(8)(9)(10)(11). The aim of this report was to assess the usefulness of BG detection (Fungitell; Associates of Cape Cod, Falmouth, MA) as a diagnostic adjunct in proven IFD in a mixed population with uncommon fungal infections due to emerging dematiaceous and hyaline septate molds (14) or with an unusual clinical presentation.…”
mentioning
confidence: 99%